Effectiveness of external myofascial mobilisation in the management of male chronic pelvic pain of muscle spastic type: A retrospective study - M. S Ajimsha (21250760) (2021)
Objective To evaluate the outcome of men with muscle spastic chronic pelvic pain syndrome (CPPS) who underwent a comprehensive five-session fascial connectivity based external myofascial mobilisation (EMM) approach. Patients and methods A retrospective chart review of patients who underwent EMM for CPPS at the Pelvic Pain Unit of Hamad Medical Corporation, Qatar between January 2019 and October 2020 was conducted. Patient’s symptoms were measured with the National Institutes of Health-Chronic Prostatitis Symptom Index (NIH-CPSI) scale and the numerical rating scale (NRS) before and after the completion of the sessions. The patients were given five EMM sessions as a ‘once-a-week’ programme. Results A total of 31 patients who completed all the EMM sessions were included. The mean (range) age of patients was 38 (20–54) years. The mean (SD) NIH-CPSI score at initial evaluation was 29.41 (8.3) and decreased to 9.14 (3.45) after the fifth visit. All the patients in the study group had a reduction of >6 points in the NIH-CPSI score, indicating a robust treatment response. The NRS reading also revealed significant improvement in pain (P < 0.001). Conclusions An EMM approach based on fascial connectivity led to significant symptom improvement in all the studied patients. EMM may be an effective treatment option for muscle spastic type of CPPS. Future high-quality studies with control groups are needed to confirm the present findings. Durability and long-term results are yet to be determined. Other Information Published in: Arab Journal of Urology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/2090598x.2021.1954414